APPLICATION OF LECTINOHISTOCHEMISTRY FOR ESTIMATION OF CHANGES OF SPINAL CORD - Sokurenko, L.M.; Chaikovsky, Yu.B. (World of Medicine and Biology, 2012)
Lectinohistochemical structure changes of spinal cord under the influence of mercury chloride small doses and correction by medications are cited in article. Monotherapy by unithiolum, thiotriazolinum, mildronatum and magne-B6 is represented. Differences in action of combinations of these medications with mildronatum are defined.